THEME STYLISTICS: EXPLORING THE POWER OF THEMES IN LITERATURE - Mamirova Shahnoza Qahramon qizi; Zilola Abduraxmonova (TADQIQOTLAR.UZ, 2023)
Abstract: Literature is a rich tapestry of words and ideas, and one of the most important elements in crafting a compelling piece of writing is the theme. Theme stylistics is the analysis and exploration of themes in literature, and it plays a crucial role in understanding and interpreting the deeper meaning of a text.